Feline pantarsal arthrodesis using pre-contoured dorsal plates applied according to the principles of percutaneous plate arthrodesis - Fitzpatrick, N.; Sajik, D.; Farrell, M. (Veterinary and Comparative Orthopaedics and Traumatology, 2013)
Objective: To describe the surgical technique for pantarsal arthrodesis (PTA) in cats according to the principles of percutaneous plate arthrodesis with application of a pre-contoured dorsal plate, without external coaptation and to report the long-term clinical outcome.Materials and methods: Retrospective review was performed of all cats treated by percutaneous plate application using a new pre-contoured dorsal plate for PTA between 2008 and 2011. Inclusion criteria were clinical and radiographic records plus clinical follow-up to at least six weeks. Data recorded included signalment, indication for surgery, postoperative care, and complications encountered. Radiographs were assessed for arthrodesis progression and complications. Outcome was assessed using an owner questionnaire.Results: Eleven cats were treated for tarsal injuries and met the inclusion criteria. Mean age was 86 ± 45 months, weight 4.50 ± 0.92 kg. The only major short-term complication encountered was wound dehiscence requiring sedation and re-suturing. In the medium-term (23.3 months ± 11.6 months) eight out of nine cats returned to normal activity and one cat showed intermittent lameness. Long-term (34.3 months ±17.5 months) radiographic evaluation was performed in seven out of nine cats; six manifested complete arthrodesis and one sustained plate breakage. Based on owner questionnaire, all nine cats returned to normal activity in the long-term, even the case with plate breakage.Conclusion: Based on our results, PTA using a custom pre-contoured dorsal plate is a suitable salvage surgery for treatment of severe tarsal injuries in cats.
Keywords: Feline; pantarsal arthrodesis; percutaneous; dorsal plate